Usefulness of five-item and three-item Mental Health Inventories to screen for depressive symptoms in the general population of Japan - Yamazaki, Shin; Fukuhara, Shunichi; Green, Joseph (Health and quality of life outcomes, 2005)
The five-question Mental Health Inventory (MHI-5) is a brief questionnaire that can be used to screen for depressive symptoms. Removing the 2 anxiety-related items from the MHI-5 yields the MHI-3. We assessed the performance of the Japanese versions of the MHI-5 and MHI-3 in detecting depressive symptoms in the general population of Japan. From the population of Japan, 4500 people 16 years old or older were selected by stratified-random sampling. The Medical Outcomes Study 36-Item Short Form Health Survey (SF-36, which includes the MHI-5) and the Zung Self-rating Depression Scale (ZSDS) were included in a self-administered questionnaire. ZSDS scores of 48 and above were taken to indicate the presence of moderate or severe depressive symptoms, and scores of 56 and above were taken to indicate the presence of severe depressive symptoms. We computed the correlation coefficient between the ZSDS score and the scores on the MHI-5 and MHI-3. We also computed the sensitivity, specificity, and area under the receiver operating characteristic (ROC) curve. Of the 3107 subjects (69% of the 4500 initially selected), 14.0% had moderate or severe depressive symptoms, and 2.0% had severe depressive symptoms as measured with the ZSDS. The correlations of ZSDS scores with MHI-5 scores and with MHI-3 scores were similar: -0.63 and -0.61, respectively. These correlation coefficients were almost the same whether or not the data were stratified by age and sex. For detecting severe depressive symptoms with the MHI-5, the area under the ROC curve was 0.942 (95%CI: 0.919 - 0.965); for the MHI-3, it was 0.933 (95%CI: 0.904 - 0.962). The MHI-5 and MHI-3 scores were correlated with the ZSDS score, and can be used to identify people with depressive symptoms in the general population of Japan.